Condition of Live Stone Coral Cover on Suprau Beach, Maladoom Mes District, Sorong City - Abdul Gofir; Roger R. Tabalessy; Tessa Rakian (INTEGRATED OF FISHERIES SCIENCE, 2024)
Coral reefs are tropical marine ecosystems that are very important for the sustainability of fishery resources and coastal protection. This study aims to evaluate the condition of live stony coral cover at Suprau Beach, Maladoom Mes District, Sorong City using the Point Intercept Transect (PIT) method. Observations were conducted at three stations at a depth of 3-5 meters. The results showed that the average live coral cover was 45.33%, which is classified as moderate. Specifically, Station I had excellent coral cover (80%) dominated by Non-Acropora corals of the Coral Branching type from the Porites family; Station II showed moderate conditions (34%) with a dominance of Non-Acropora corals of various life forms; and Station III was in a damaged condition (20%) with high coverage of dead corals covered with algae (52%) and sand (24%). Water quality conditions at all three stations still support coral growth, with parameters such as temperature (29-32°C), salinity (31-35 ppt), pH (7.5 ppt), and water clarity (4-8.5 m) within the optimal range. High sedimentation at Stations II and III is the main factor limiting coral growth, caused by community activities such as beach reclamation, pier construction, and hill excavation around the waters. This study provides basic information for the development of strategies for the rehabilitation and management of coral reef ecosystems in Sorong City.